2012
DOI: 10.1056/nejmoa1200850
|View full text |Cite
|
Sign up to set email alerts
|

Waning Protection after Fifth Dose of Acellular Pertussis Vaccine in Children

Abstract: Protection against pertussis waned during the 5 years after the fifth dose of DTaP. (Funded by Kaiser Permanente).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
319
3
28

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(366 citation statements)
references
References 19 publications
16
319
3
28
Order By: Relevance
“…Although some first-generation acellular vaccines had poor immunity and efficacy, double-blinded clinical trials and field-efficacy studies for the US-licensed acellular vaccines estimated the short-term efficacy to be excellent: ∼85% after three doses and 98% after five doses (28)(29)(30). However, recent cohort and case-control studies concluded that 5 y following the fifth aP dose, children are fourfold to 15-fold more likely to acquire pertussis compared with within the first year, consistent with waning aP immunity (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Although some first-generation acellular vaccines had poor immunity and efficacy, double-blinded clinical trials and field-efficacy studies for the US-licensed acellular vaccines estimated the short-term efficacy to be excellent: ∼85% after three doses and 98% after five doses (28)(29)(30). However, recent cohort and case-control studies concluded that 5 y following the fifth aP dose, children are fourfold to 15-fold more likely to acquire pertussis compared with within the first year, consistent with waning aP immunity (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Although the basis of this is still not fully clear, resurgence of pertussis is prominent in countries using acellular pertussis (aP) vaccines. It is becoming more evident that aP vaccines do not induce long lasting protection [1] and studies in animal models have suggested that aP vaccination fails to prevent nasal colonization and transmission of B. pertussis [2]. Studies in a baboon challenge model showed that immunization with an alum-formulated aP vaccine protected animals from disease, but did not prevent nasal colonization or bacterial transmission to naïve animals; nasal colonization in these animals lasted at least as long as that in unvaccinated controls [2].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors likely contribute to increased disease reporting, including heightened awareness, expanded surveillance, improved laboratory diagnostic testing, and allelic mismatch between circulating and vaccine reference strains (2,4,5). Waning protection conferred by acellular vaccine formulations, which replaced whole-cell preparations in the United States during the 1990s, has also led to increased disease rates among vaccinated individuals (2,(6)(7)(8).…”
mentioning
confidence: 99%